PENGARUH SULFUR TERHADAP KARAKTERISTIK MARSHALL ASPHALTIC CONCRETE WEARING COURSE (AC-WC) - Setiawan, Arief (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Improving the quality of petroleum asphalt is required to obtain the characteristicmix asphalt is better so than pavement thickness becomes thinner also provide a longer service life.One of the added material used is Sulfur. The addition of Sulfur to the asphalt, better known as SulfurExtended Asphalt (SEA) as a partial substitution of hard asphalt. The purpose of this study was todetermine the effect of Sulfur on the characteristics of AC-WC mixture.The study was conducted by giving the variation of sulfur content of 0%, 3%, 5% and 7% of the weightof asphalt. Aggregate taken from the Taipa River with a choice of AC-WC finely graded based on theGeneral Specifications of Bina Marga in 2010. Gradation based targeting by portion, forimplementation in a laboratory controlled by sieve. Testing characteristics of the mixture usingMarshall. Kruskal-Wallis test with SPSS version 17 conducted to determine the effect of Sulfur on thecharacteristics of Marshall.The results obtained, in general that the addition of Sulfur increases the need for optimum bitumencontent (OBC). Based on Kruskal-Wallis test shows that the Sulfur had a significant influence on thestability, density, VMA and flow at 95% confidence level. Optimum asphalt content at 0%, 3% and 5%is 5.65%, 6.18% and 5.85% respectively. At 7% bitumen content could not be determined the OptimumBitumen Content value. Marshall stability increased by 13.37% (1935.331 kg) and 17.65% (2008.328 kg)on the sulfur content of 3% and 5%, to specimen control 0% sulfur (1707.054 kg).